A theoretical study of the radical scavenging activity of natural stilbenes. Issue 72 (18th December 2019) - Vo, Quan V.; Cam Nam, Pham; Bay, Mai Van; Minh Thong, Nguyen; Hieu, Le Trung; Mechler, Adam
Abstract : Oxidative stress is implicated in aging and aging-related diseases, including cancer. Abstract : Oxidative stress is implicated in aging and aging-related diseases, including cancer. Prevention-focused health management approaches emphasize the importance of dietary antioxidants, which naturally draws attention to the antioxidant capacity of natural products. Several groups of plant-derived antioxidant compounds have been identified and their radical scavenging activity confirmed and measured; it has proven challenging, however, to link the experimentally determined activity quantitatively to a molecular mechanism of action. Based on our success with a computational approach, in this study, the methylperoxyl radical scavenging activity of 12 natural stilbenes was evaluated based on kinetic and thermodynamic calculations. The results suggest that for stilbenes hydrogen atom transfer (HAT) is a main mechanism for the ROO˙ radical scavenging in the gas. Assessing the role of substitutes on the antioxidant properties of stilbenes revealed that the presence of O–H groups in ring B can increase the antioxidant activity due to a decrease in the bond dissociation energy (BDE) of the O4′–H, while the replacement of a H atom in the O–H groups by a methyl group reduces the radical scavenging capacity. Among the studied compounds, astringin is a promising antioxidant with the low BDE(O–H) value (73.4 kcal mol −1 ) and the high rate constants (3.36 × 10 6, 4.11 × 10 3 and 9.31 × 10 8 M −1 s −1 in the gas phase, pentyl ethanoate and water, respectively) that suggest higher activity than trans -resveratrol.